2011
DOI: 10.1016/j.jmii.2010.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans versus non-albicans bloodstream infections: The comparison of risk factors and outcome

Abstract: The outcome of candidemia was poor. The identified risk factors may help us to differentiate fatal candidemia in early infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
59
3
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 35 publications
9
59
3
4
Order By: Relevance
“…A high sensitivity of C. albicans to antifungal agents was observed, corroborating other published works 6,12,31 . As observed in Table 3, among the NCAC species (n=32), 31.2% of the isolates demonstrated SDD to fl uconazole, with 3.1% being resistant to amphotericin B (which corroborates published reports of high resistance of these species to antifungal agents) 9,13 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A high sensitivity of C. albicans to antifungal agents was observed, corroborating other published works 6,12,31 . As observed in Table 3, among the NCAC species (n=32), 31.2% of the isolates demonstrated SDD to fl uconazole, with 3.1% being resistant to amphotericin B (which corroborates published reports of high resistance of these species to antifungal agents) 9,13 .…”
Section: Discussionsupporting
confidence: 90%
“…In Brazil and in our study, several studies have indicated C. tropicalis as the second most frequent isolate in cases of candidemia among hospitalized patients 12,20,24 . C. tropicalis is the fourth most frequent Candida species isolated in cases of candidemia in the United States 30 and the third most frequent isolate in Spain 8 and Asia 6 . The ability to detect bloodstream infections caused by Candida spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the most common diseases that predispose to an increased sensitivity to C. albicans overgrowth are diabetes mellitus, cancer, leukemia, AIDS, thyroid dysfunction and other diseases, in which host defense mechanisms are suppressed or adrenal cortex steroids/antibiotics/other similar drugs are used (immunosuppressed patients) [6,10,12,24,25,37,40,53,56,[70][71][72].…”
Section: Impaired Immune System and Underlying Disease Statesmentioning
confidence: 99%
“…NAC species are of special concern because of their high drug-resistance and increasing prevalence in invasive candidiasis [7]. Several years ago, different studies have been reported about candidemia in hospitals of Saudi Arabia, and these studies have used different designs, prospective vs. retrospective and different patient groups (ICU vs. non-ICU) [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%